Consumer Behavior of Middle-Income Class Towards The Utilization of Medicinal Plants During The Covid-19 Pandemic - Dudi Septiadi; Pande Komang Suparyana; Sharfina Nabilah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Since the outbreak of Covid-19 in Indonesia, medicinal plants have become viral and are in great demand by the public. The application of healthy living behavior by consuming medicinal plants is one of the efforts for the community to maintain health and increase immunity. The objectives of th is research are to; 1) explain the development and role of the middle-income class in the Indonesian economy; 2) analyze middle-class behavior related to the literacy level of middle-income class society; 3) analyze the behavior of the middle-income class in consuming medicinal plants as an effort to increase immunity. The research method used in this research is a descriptive qualitative approach. The number of samples used in the study is 90 respondents. Based on the research results, it shows that the growth of the middle-income class from 2012 to 2020 has increased by 64% to 68.2 million people. A large number of middle-class people in Indonesia have played a role in supporting the domestic economy in terms of consumption expenditure. Based on this research, the highest number were middle-class people with moderate levels of literacy, which is 44 percent. Middle-class people who have a high literacy rate are as much as 25 percent. Meanwhile, the middle-class people with low literacy levels are quite a lot, namely 31 percent. The interest of the middle class in consuming medicinal plants is relatively high. There were 32 middle-class respondents who had a high interest in consuming medicinal plants during the Covid-19 Pandemic.